Parasitofauna of the Caspian salmon (Salmo trutta caspius Kessler) at the salmon fish hatcheries of Azerbaijan for the period of their existence - Ibrahimova, N.; Rzayev, F. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
The Caspian salmon is included in the Red List of Azerbaijan with the international status CR (Critically Endangered). The article presents the comparative analysis of the parasitofauna of the Caspian salmon (Salmo trutta caspius Kessler) during the period of its existence (1955–2015) at the hatcheries of Azerbaijan (Chaykend and Chukhur-Gabala salmon fish hatcheries). When comparing the quantitative index of parasitofauna for the first years after the creation of the salmon fish hatcheries (9 species of parasites) and studies carried out by the authors (7 species of parasites), it was revealed that the change was insignificant. However, significant changes in the species composition of the parasitofauna of the Caspian salmon were found. The parasites Chilodonella piscicola, Trichodina truttae, Eubothrium crassum, Rhabdochona gnedini, Cystidicoloides tenuissima, Piscicola geometra found in the first years of the salmon fish hatcheries were not recorded by the authors, and Bunodera luciopercae, Metechinorhynchus baeri, Pomphorhynchus laevis, Glochidium sp. revealed in recent studies were not observed in the early years. The dominant groups of parasites of the Caspian salmon were revealed. A systematic review of all parasites of salmonids found during this period is presented. Three species of parasites were noted for the first time in the territory of Azerbaijan for the Caspian salmon in the salmon fish hatcheries (trematode Bunodera luciopercae, acanthochephala Pomphorhynchus laevis and mollusk Glochidium sp.). The authors specifically noted parasites identified from 2005 to 2015 that are conditionally pathogenic for the Caspian salmon and capable to cause significant damage to the salmon hatcheries: Costia necatrix, Ichthyophthyrius multifiliis, Gyrodactylus derjavini, Metechinorhynchus baeri, Pomphorhynchus leavis, Bunodera luciopercae. The authors note that during the period of parasitological studies of the Caspian salmon in salmon hatcheries in Azerbaijan, pathogenic parasites for humans have not been found.